2016
DOI: 10.19044/esj.2016.v12n5p100
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related To Job Satisfaction Among Nurses

Abstract: Background: The level of job satisfaction affects not only the quality of the function exercised by the nurse, but also patient satisfaction, therefore it is very important for health care institutions to measure these perceptions amongst nurses. Aim of the study: This research had assessed the job satisfaction among nurses in the Public Hospital Vlora, Albania and the contributing factors on it. Method: Data of this cross-sectional research were collected using a questionnaire which measures job satisfaction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…In contrast to this, the findings of the study conducted in Vlora State Hospital showed that the most important intrinsic factors that affect job satisfaction was career growth (mean score=3.84) and the most important extrinsic factor that affect the job satisfaction was monthly salary (mean score=4.5). 11 This might be because of difference in the sampling technique, sample size and use of different instrument.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this, the findings of the study conducted in Vlora State Hospital showed that the most important intrinsic factors that affect job satisfaction was career growth (mean score=3.84) and the most important extrinsic factor that affect the job satisfaction was monthly salary (mean score=4.5). 11 This might be because of difference in the sampling technique, sample size and use of different instrument.…”
Section: Discussionmentioning
confidence: 99%
“…26 Many factors can affect job satisfaction, including the work conditions, internal relationships in the practice environment, workload, scheduling, entrusted duties, acknowledgement and respect, salary, self-growth and promotion, responsibility and job security, leadership styles and organizational policies, 27 empowerment of the employees, 28 and nurses’ level of education and work shifts. 29,30 Job satisfaction also improves the quality of life in nurses 31 and enhances the quality of nursing care provided and reduces job burnout, 32 emotional exhaustion, 33 job turnover, 34 patient dissatisfaction, 32 and ultimately, infections in patients. 35 Poor job satisfaction exposes nurses to certain diseases in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Job satisfaction has been defined as the feelings and attitude of people towards their work [1]. It is a significant indicator of the way nurses feel about their profession, the efforts to perform their professional duties, or otherwise abandons it willingly [2]. It also refers to how well a work provides gratification of a need or how well it provides a means of self-gratification.…”
Section: Background Of the Studymentioning
confidence: 99%